Livestock innovation systems and networks: Findings from smallholder dairy farmers in Ethiopia - Asres, A.; Sölkner, Johann; Puskur, Ranjitha; Wurzinger, Maria (2012)
This paper uses household and key informant survey data from Ethiopia to: (1) understand the organizational structures that influence change in dairy production systems; (2) explore how local-level innovation system networks are functioning in the smallholder dairy production and (3) identify intervention points for strengthening innovation capacity. Results revealed that public sector actors are the major role players in the dairy production system despite their minor role in marketing linkages. We also found out that the private sector actors play peripheral roles in the network. Differences between innovator and non-innovator social networks were observed, with innovators exhibiting greater access to sources of production knowledge, inputs, credits and markets. Important institutions that could strengthen the stakeholders’ ability to identify, implement and adapt sustainable practices were not included in the processes. We recommend for policy guidance to reform the current agricultural extension system to address institutional and policy issues that constrain effective agricultural innovation system.